Role of Recommendation Systems in Digital Music Streaming Platforms: User Decision-Making Among Sampoerna University Students - Marina Indira Candera; Tika Endah Lestari (Fakultas Teknik Universitas Persada Indonesia YAI, 2026)
This study explored the influence of recommendation systems in digital music streaming platforms on the decision-making processes of students at Sampoerna University. Utilizing a socio-technical framework, the research examined the tension between algorithmic efficiency and user exploration. Data were collected via a quantitative survey of 41 students, which revealed that while platforms like Spotify (80.5%) and YouTube Music (51.2%) were dominant, users experienced a distinct